Особенности механизма нормирования устной публичной речи на фонетическ:ом (сегментном) уровне - ВЕЩИКОВА, ИРИНА (Stylistyka, 2021)
There are two opposite points of view on structure of norm of oral puЫic language in modem linguistics. According to first of them all sphere OPL is attended Ьу codified language. The second point of view contends that OPL is comЬination of codified noпn and spoken one. А new approach to proЫem of norm of OPL and to normalized interpretation of spoken language phonetics is proposed in this article.